Gut immune stimulation by non pathogenic Gram(+) and Gram(-) bacteria. Comparison with a probiotic strain - Dogi, Cecilia Ana (2008)
We analyzed the gut immune stimulation induced by Gram-positive bacteria: non probiotic Lactobacillus acidophilus CRL 1462 and Lactobacillus acidophilus A9; two potentially probiotic strains: L. acidophilus CRL 924 and Lactobacillus delbrueckii subsp. bulgaricus CRL 423; comparatively with a probiotic strain: Lactobacillus casei CRL 431. We also studied Gram-negative bacteria: Escherichia coli 129 and E. coli 13-7 in BALB/c mice. All the strains increased the number of IgA+ cells. We analyzed the cytokines IFNγ, TNFα, IL-17, IL-12, IL-6 and MIP-1α. The Gram(+) strains increased the number of IL-10+ cells. Gram(-) strains did not increase IL-10+ cells, but they increased the number of IL-12+ cells. The probiotic strain increased mainly IFNγ and TNFα. In the study of the receptors TLR-2, TLR-4 and CD-206, we demonstrated that only the probiotic strain increased the number of CD-206+ cells. All the Gram(+) strains increased the number of TLR-2+ cells and the Gram(-) strains of the TLR-4+ cells. The probiotic strain induced the release of IL-6 by a preparation enriched in intestinal epithelial cells (IEC). Gram(+) and Gram(-) bacteria activated different immune receptors and induced a different cytokine profile. The probiotic strain showed a great activity on the immune cells and the enriched population in IEC, activating mainly cells of the innate immune system. © 2007 Elsevier Ltd. All rights reserved.